Menganalisis Pengucapan Bahasa Indonesia dan Bahasa Papua - Yorensina Anip Kalakmabin; Heri Isnaini (Pragmatik : Jurnal Rumpun Ilmu Bahasa dan Pendidikan, 2023)
This research is a case study research. The sampling technique is purposive sampling. Data sources used are events, informants, and documents. Data collection techniques are carried out by direct observation, interviews, and documents. The test of data validity used is source triangulation and method triangulation. The data analysis technique used is flow model data analysis. The results of this study are descriptions of: (1) the characteristics of Papuan accent Indonesian are distinguished based on linguistic and nonlinguistic elements. Linguistic elements include; (a) phoneme replacement; (b) diphthong replacement; (c) phoneme completion; (d) the use of intonation. Nonlinguistic elements are speech events and paralinguistics; (2) factors that influence the emergence of Papuan characteristics Indonesian accents, namely; (a) administrative units; (b) a special sense of community identity; (c) reside in the same geographical area; (d) historical experience; (3) Indonesian Papuan accent has relevance as teaching material for sociolinguistic courses in the Indonesian Education Study Program.